EVALUASI FAKTOR-FAKTOR YANG BERKONTRIBUSI DALAM PERENCANAAN KEUANGAN MAHASISWA STIE SURAKARTA - Saputra, Era Trianita; Saharsini, Astuning; Octavia, Dewi Ika; Susanti, Ari (Program Studi Akuntansi Fakultas Ekonomi Universitas Sarjanawiyata Tamansiswa, 2025)
Financial literacy plays a very important role in personal financial planning, especially in the context of the digital era which is full of increasingly complex financial products and services. An individual's understanding of basic financial concepts, such as managing income, expenses, savings, investments, and debt, is the main key to making smart financial decisions. This study was conducted on accounting students at the Surakarta College of Economics. This study is a study with a quantitative approach. The population in this study were active accounting students at STIE Surakarta who were registered with PDDikti in 2024, totaling 495 students. The sampling technique in this study used a purposive sampling technique. The sample of this study was 59 respondents. The results of the study showed that financial literacy and social environment had an effect on financial planning. In addition, investment motivation did not affect financial planning